Intrapleural Injection of Anti-PD1 Antibody: A Novel Management of Malignant Pleural Effusion - Li, Xinying; Wu, Guannan; Chen, Cen; Zhao, Yuan; Zhu, Suhua; Song, Xincui; Yin, Jie; Lv, Tangfeng; Song, Yong (Frontiers in Immunology, 2021)
Background: Malignant tumors accompanied with malignant pleural effusion (MPE) often indicate poor prognosis. The therapeutic effect and mechanism of intrapleural injection of anti-programmed cell death protein 1 (PD1) on MPE need to be explored. Methods: A preclinical MPE mouse model and a small clinical study were used to evaluate the effect of intrapleural injection of anti-PD1 antibody. The role of immune cells was observed via flow cytometry, RNA-sequencing, quantitative PCR, western blot, immunohistochemistry, and other experimental methods. Results: Intrathoracic injection of anti-PD1 monoclonal antibody (mAb) has significantly prolonged the survival time of mice (P = 0.0098) and reduced the amount of effusion (P = 0.003) and the number of cancer nodules (P = 0.0043). Local CD8+ T cells participated in intrapleural administration of anti-PD1 mAb. The proportion of CD69+, IFN-γ+, and granzyme B+ CD8+ T cells in the pleural cavity was increased, and the expression of TNF-α and IL-1β in MPE also developed significantly after injection. Local injection promoted activation of the CCL20/CCR6 pathway in the tumor microenvironment and further elevated the expression of several molecules related to lymphocyte activation. Clinically, the control rate of intrathoracic injection of sintilimab (a human anti-PD1 mAb) for 10 weeks in NSCLC patients with MPE was 66.7%. Local injection improved the activity and function of patients’ local cytotoxic T cells (CTLs). Conclusions: Intrapleural injection of anti-PD1 mAb could control malignant pleural effusion and the growth of cancer, which may be achieved by enhancing local CTL activity and cytotoxicity.